2016
DOI: 10.1016/j.drugalcdep.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Using eye-tracking to examine how embedding risk corrective statements improves cigarette risk beliefs: Implications for tobacco regulatory policy

Abstract: Background Tobacco companies have deliberately used explicit and implicit misleading information in marketing campaigns. The aim of the current study was to experimentally investigate whether the editing of explicit and implicit content of a print advertisement improves smokers’ risk beliefs and smokers’ knowledge of explicit and implicit information. Methods Using a 2(explicit/implicit) x 2(accurate/misleading) between-subject design, 203 smokers were randomly assigned to one of four advertisement condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…This could be because smokers were exposed to the PWL only and not to a cigarette pack or advertisement that included the PWL. Previous research has shown that smokers latency to text is relatively long when included in a cigarette advertisement, 21 exceeding the average total viewing time of a print ad. 33 It remains unclear why smokers in the congruent condition focused faster on the image than smokers in the incongruent condition.…”
Section: Discussionmentioning
confidence: 96%
“…This could be because smokers were exposed to the PWL only and not to a cigarette pack or advertisement that included the PWL. Previous research has shown that smokers latency to text is relatively long when included in a cigarette advertisement, 21 exceeding the average total viewing time of a print ad. 33 It remains unclear why smokers in the congruent condition focused faster on the image than smokers in the incongruent condition.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with previous work (Lochbuehler et al, 2016; Shadel et al, 2006; Strasser et al, 2012; Strasser et al, 2008), participants viewed an unaltered company-created advertisement for 30 seconds (Strasser et al, 2008), deliberately presented five days before randomization to approximate real-world conditions (e.g., viewing novel product advertisement in a magazine/online/etc., then purchasing it the next time at store; i.e., not immediately after viewing advertisement).…”
Section: Methodsmentioning
confidence: 89%
“…Eight items (Lochbuehler et al, 2016; Shadel et al, 2006; Strasser et al, 2008) rated on a 5-point response scale (1= “definitely untrue”, 5=“definitely true”) assessed participants’ Quest cigarette beliefs only at the initial study visit, before and after viewing the advertisement: “Quest cigarettes:” (a) “are lower in nicotine than regular cigarettes”, (b) “are lower in tar than regular cigarettes”, (c) “are less addictive than regular cigarettes”, (d) “are less likely to cause cancer than regular cigarettes”, (e) “have fewer chemicals than regular cigarettes”, (f) “healthier than regular cigarettes”, (g) “make smoking safer”, (h) “help people quit smoking.” Items b–h were summed to create a cumulative false beliefs variable (Cronbach’s α’s = 0.77 and 0.81 for pre- and post-advertisement variables, respectively); consistent with previous work (Lochbuehler et al, 2016; Shadel et al, 2006), the first item was excluded because it was factually correct.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, findings did not depend on the study methodology that was used. Finally, the current studies measured visual attention to warning statements, which has been shown to predict product choice (Bialkova et al, 2014) and risk perceptions (Lochbuehler et al, 2016).…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 99%